BAHAN AJAR WRITING FOR ACADEMIC PURPOSES BERBASIS SELF-MOTIVATED LEARNING - Imroatus Solikhah (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2014)
This study is aimed at devising teaching materials for Writing for Academic Purposes (WAP). In context of English for Academic Purposes (EAP), writing is the core materials together woth reading comprehension and critical thinking. The study used Recursive Reflective Design and Development (R2D2) from Willis (1995). The main data if this study were writing materials for academic purposes and the subjects of the study included lecturer, students, and expert in writing. The study revealed two main ifndings. In the Defining Stage, the findings indicated that WAP should include writing for academic purposes that start from paragraph, three paragraph-composition, and 3-5 paragraph essay. The model of the essay is argumentative or persuasive essay as it is applicable for Test of Written English (TWE) for the TOEFL. In the Design and Development Stage, the WAP materials were developed into four components of instructional design: Competency Standard, Basic Competency, Indicators, and Core Materials. In overall outline, the design of WAP is begun with paragraph and its component and the essay for TWE.